Positive electrode active material, preparation method thereof and battery
By using secondary particles formed by the accumulation of primary particles, the core and shell layer contain conductive carbon materials and iron elements, the problem of metal dissolution and capacity maintenance of lithium-ion polyanion positive electrode materials at high temperatures is solved, and better low-temperature capacity and high-temperature cycling performance are achieved.
Patent Information
- Application Number
- CN202411763740.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-11
AI Technical Summary
Lithium-ion polyanionic cathode materials have defects such as low electron conductivity and lithium-ion diffusion rate, and easy dissolution of high-temperature metals, which affect the capacity of the material and the capacity maintenance at high temperatures.
Secondary particles are used that accumulate primary particles. The secondary particles include a core and a shell layer. The conductive carbon material is located in the core and shell layer and contains iron elements to ensure that the conductive carbon material is not destroyed during the synthesis of the positive electrode sheet, keep the electronic network connected, and inhibit metal dissolution.
It improves the capacity and energy performance of the battery at low temperatures, and improves the storage and circulation performance at high temperatures, ensuring the structural integrity of the positive electrode active material.
Smart Images

Figure CN119601627A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode active material and a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion polyanion cathode materials have the advantages of good safety, high theoretical specific capacity, stable structure, environmental friendliness, and abundant resources. However, lithium-ion polyanion cathode materials have defects such as low electronic conductivity and lithium-ion diffusion rate, and easy dissolution of high-temperature metals, which seriously affect the capacity of this type of material and the capacity retention at high temperatures.
[0003] In order to improve the electronic conductivity of lithium ion polyanion positive electrode materials and reduce metal dissolution, the surface of positive electrode particles is usually carbon-coated. In order to increase the lithium ion diffusion rate, the particle size of the primary particles needs to be reduced. However, reducing the size of the primary particles will lead to an increase in the specific surface area of the material. Gel phenomenon is likely to occur during the positive electrode homogenization process, making it difficult to process. Making the dispersed primary particles into agglomerated secondary particles can not only ensure the lithium ion diffusion rate, but also reduce the specific surface area of the positive electrode material, which can effectively improve the processing problems during the positive electrode homogenization process. However, during the synthesis of the electrode sheet, the carbon coating structure on the surface is destroyed due to the mutual extrusion between the secondary particles, affecting the distribution of the conductive network between the particles, and ultimately affecting the capacity and retention of the battery during charging and discharging at extreme temperatures. Summary of the invention
[0004] The present invention provides a positive electrode active material, the positive electrode active material comprises primary particles and secondary particles, the secondary particles are formed by stacking the primary particles. The secondary particles comprise a core and a shell layer located on the surface of the core, the conductive carbon material of the positive electrode active material will not be destroyed during the synthesis of the positive electrode sheet, the connectivity of the electronic network of the battery during the charging and discharging process can be ensured, the charge transfer impedance at low temperature can be effectively reduced, thereby ensuring the low temperature performance of the battery, and at the same time, since the secondary particles of the positive electrode active material are a unique core-shell structure, the metal dissolution can be effectively inhibited, the integrity of the positive electrode active material structure can be ensured, thereby effectively improving the high temperature performance of the battery.
[0005] The present invention also provides a method for preparing the positive electrode active material. The method can prepare the positive electrode active material and is simple to operate.
[0006] The present invention also provides a battery comprising the above-mentioned positive electrode active material, which is suitable for a starting power supply, has smaller polarization at low temperatures, better cold start and discharge capacity, and better storage and cycle performance at high temperatures.
[0007] In detail, in the first aspect, the present invention provides a positive electrode active material, which includes primary particles and secondary particles formed by accumulation of primary particles, wherein the secondary particles include an inner core and a shell located on the surface of the inner core, and the inner core and the shell include a conductive carbon material, and the mass content of iron in the conductive carbon material is 0.5ppm to 45ppm.
[0008] Furthermore, the porosity of the inner core is 5% to 30%, and / or the porosity of the shell layer is 2% to 15%, and / or the porosity of the inner core is greater than the porosity of the shell layer.
[0009] Furthermore, the thickness of the shell layer is m, the average particle size of the core is n, and n and m satisfy: 1≤n / m≤50;
[0010] and / or, m is 1 μm-5 μm; preferably 1 μm-3 μm;
[0011] And / or, n is 3 μm-15 μm; preferably 4 μm-10 μm.
[0012] Furthermore, based on the total mass of the positive electrode active material, the percentage content of the conductive carbon material in the shell layer is f, and f satisfies: 2%≤f≤8%;
[0013] And / or, based on the total mass of the positive electrode active material, the percentage content of the conductive carbon material in the inner core is h, and h satisfies: 4%≤h≤10%;
[0014] And / or, the percentage content f of the conductive carbon material in the shell layer is less than the percentage content h of the conductive carbon material in the core layer.
[0015] Furthermore, the D50 of the secondary particles is 3 to 15 μm, and the average particle size of the primary particles is 200 to 400 nm.
[0016] Furthermore, the average particle size of the conductive carbon material is 10 to 100 nm.
[0017] and / or, the conductive carbon material comprises carbon black,
[0018] And / or, the chemical formula of the positive electrode active material is LiFe x M 1-x PO4; wherein M is at least one of Mn, Co, Ni, and V, and 0≤x≤1.
[0019] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:
[0020] A mixture of conductive carbon material, organic carbon source, iron source, M source, lithium source, phosphorus source and solvent is stirred and ball-milled, and then spray-dried at 0.3-0.8 MPa to obtain a precursor of a positive electrode active material, and then sintered at 700-900° C. for 15-30 hours to obtain a positive electrode active material; wherein the solid content of the mixture is not higher than 40wt%.
[0021] In a third aspect, the present invention provides a battery comprising a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises a current collector and a positive electrode active material layer coated on at least one surface of the current collector, wherein the positive electrode active material layer comprises the positive electrode active material described in the first aspect.
[0022] Furthermore, the negative electrode sheet comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises graphite, at least a portion of the surface of the graphite is coated with a soft carbon layer, and the thickness of the soft carbon layer is less than 30 nm.
[0023] Furthermore, the mass content of iron in the soft carbon layer is a, the mass content of iron in the conductive carbon material in the positive electrode active material is b, and a and b satisfy: 2≤b / a≤10;
[0024] a is 0.1ppm-30ppm, preferably 2ppm-15ppm;
[0025] b is 0.5ppm-45ppm, preferably 5ppm-20ppm.
[0026] The positive electrode active material provided by the present invention is composed of secondary particles formed by the accumulation of primary particles, and the secondary particles include a core and a shell, and the core and the shell contain a conductive carbon material. Different from the structure of the surface of the traditional positive electrode active material coated with a conductive carbon material, the conductive carbon material of the present invention will not be destroyed during the rolling process of the positive electrode sheet, and can be completely retained in the core and shell of the secondary particles of the positive electrode active material, thereby ensuring the connectivity of the electronic network between the positive electrode active materials during the charge and discharge process, so that the battery made therefrom can exert higher capacity and energy at low temperatures; secondly, the positive electrode active material of the present invention includes secondary particles, and the secondary particles are a core-shell structure. The structure of the shell is denser than that of the core, and the conductive carbon material of the core and the shell includes a certain amount of iron; on the one hand, the dense shell structure can prevent too much electrolyte from entering the secondary particles. The inner part of the core can prevent the destruction of the structure of the positive electrode active material due to excessive contact between the electrolyte and the positive electrode active material. At the same time, the dense shell structure can also prevent the metal elements dissolved from the core from entering the negative electrode through the electrolyte and being reduced on the surface of the negative electrode, thereby causing safety hazards. On the other hand, the conductive carbon material includes a certain amount of iron element. The iron element contacts the metal elements in the positive electrode active material and the electrolyte, and can react with the electrolyte. Competition is formed between them, thereby reducing the metal dissolution of the positive electrode active material, further protecting the structural integrity of the positive electrode active material, and helping to improve the high temperature characteristics of the battery, such as high temperature storage and high temperature cycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 This is a microscopic morphology of the positive electrode active material of Example 1 of the present invention;
[0029] Figure 2 This is a cross-sectional microscopic morphology of the positive electrode active material of Example 1 of the present invention;
[0030] Figure 3 This is a schematic diagram of the identification of the core and shell of the positive electrode active material of Example 1 of the present invention;
[0031] Figure 4 This is an EDS spectrum of the iron element of the positive electrode active material of Example 1 of the present invention;
[0032] Figure 5 This is an EDS spectrum of oxygen element of the positive electrode active material of Example 1 of the present invention;
[0033] Figure 6 This is an EDS spectrum of phosphorus element of the positive electrode active material of Example 1 of the present invention;
[0034] Figure 7 This is an EDS spectrum of carbon element of the positive electrode active material of Example 1 of the present invention;
[0035] Figure 8 is a cross-sectional morphology diagram of a positive electrode sheet including the positive electrode active material of Example 1;
[0036] Fig. 9 1 is a low-temperature discharge curve of a battery including the positive electrode active materials of Comparative Example 1 and Example 1. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] In a first aspect, the present invention provides a positive electrode active material, which includes primary particles and secondary particles formed by accumulation of the primary particles, wherein the secondary particles include an inner core and a shell located on the surface of the inner core, wherein the inner core and the shell include a conductive carbon material, and the mass content of iron in the conductive carbon material is 0.5ppm to 45ppm.
[0039] The positive electrode active material of the present invention helps to improve the capacity development and maintenance of the battery during the charge and discharge process at extreme temperatures. The main reasons include: first, unlike the traditional structure in which the conductive carbon material is coated on the surface of the positive electrode active material, the conductive carbon material in the present invention is located in the core and shell of the secondary particles in the positive electrode active material. The conductive carbon material of the present invention will not be destroyed during the rolling process of the positive electrode sheet, and can be completely retained in the core and shell of the secondary particles of the positive electrode active material, which can ensure the connectivity of the electronic network between the positive electrode active materials during the charge and discharge process, so that the battery made therefrom can exert higher capacity and energy at low temperatures; second, the secondary particles of the present invention are core-shell structures, and the structure of the shell is denser than that of the core. The dense shell structure can prevent too much electrolyte from entering the interior of the secondary particles, thereby preventing the intensification of side reactions due to excessive contact between the electrolyte and the positive electrode active material, and then causing the destruction of the structure of the positive electrode active material. The dense shell structure can also prevent the metal elements dissolved from the inner core from entering the negative electrode through the electrolyte and being reduced on the negative electrode surface to cause safety hazards. Thirdly, the iron element in the conductive carbon material and the metal elements (such as Fe) in the positive electrode active material are in contact with the electrolyte and can react with the electrolyte. Competition occurs between them, thereby reducing the metal dissolution of the positive electrode active material, further protecting the structural integrity of the positive electrode active material, and helping to improve the high temperature characteristics of the battery, such as high temperature storage and high temperature cycling.
[0040] In some embodiments, the secondary particles are secondary spherical particles. In some embodiments, the content of iron in the conductive carbon material can be measured by inductively coupled plasma spectrometer (ICP) or energy dispersive spectrometer (EDS).
[0041] Exemplarily, the iron concentration in the conductive carbon material is 0.5ppm, 1ppm, 2ppm, 3ppm, 4ppm, 5ppm, 6ppm, 7ppm, 8ppm, 9ppm, 1ppm, 11ppm, 12ppm, 13ppm, 14ppm, 15ppm, 16ppm, 17ppm, 18ppm, 19ppm, 20ppm, 21ppm, 22ppm, 23ppm, 24ppm, 25ppm, 26ppm, 27ppm, 28ppm, 29ppm, 30ppm, 31ppm, 32ppm, 33ppm, 34ppm, 35ppm, 36ppm, 37ppm, 38ppm, 39ppm, 40ppm, 41ppm, 42ppm, 43ppm, 44ppm, 45ppm, any value among the above, or a range consisting of any two of the values.
[0042] In a specific embodiment, the conductive carbon material contains 5-20 ppm of iron.
[0043] The source of the iron element in the conductive carbon material is not particularly limited in the present invention. In some embodiments, the iron element is derived from an iron-based catalyst introduced during the synthesis of the conductive carbon material.
[0044] The above-mentioned conductive carbon material can be purchased directly on the market or prepared by existing methods. In a specific embodiment, the conductive carbon material is carbon black, which is prepared by catalytic oil slurry. Furthermore, by using an iron catalyst, waste rubber or other substances with a high carbon content are converted into carbon black, and then the residual iron content is controlled through an impurity removal process, so that carbon black with different iron content can be obtained.
[0045] In a specific embodiment, the porosity of the inner core is 5% to 30%, and / or the porosity of the shell layer is 2% to 15%, and / or the porosity of the inner core is greater than the porosity of the shell layer.
[0046] Among them, the porosity of the inner core is 5% to 30%, which can provide more lithium ion storage space for the positive electrode active material, is conducive to the rapid transmission of lithium ions, and reduces the stress concentration and particle breakage caused by the volume change of the positive electrode active material during the battery charging and discharging process; the porosity of the shell is 2%-15%, and the dense shell structure can also prevent the metal elements dissolved from the core from entering the negative electrode through the electrolyte and being reduced on the negative electrode surface, causing safety hazards; the porosity of the inner core is greater than the porosity of the shell, which can further prevent too much electrolyte from entering the secondary particles, thereby preventing the increase of side reactions due to excessive contact between the electrolyte and the positive electrode active material.
[0047] Exemplarily, the porosity of the inner core is any value among 5%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, etc., or a range consisting of any two of them, and the porosity of the shell layer is any value among 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, etc., or a range consisting of any two of them.
[0048] The porosity of the inner core may be tested by cutting the secondary particle from the middle, performing cross-sectional backscattering SEM on the cut secondary particle, and measuring the ratio of the pore area of the cross section of the inner core of the secondary particle to the total area of the spherical cross section, which is the porosity of the inner core;
[0049] The porosity of the shell layer can be tested by: cutting the secondary particle from the middle, performing cross-sectional backscattering SEM on the cut secondary particle, and measuring the ratio of the pore area of the cross section of the shell layer of the secondary particle to the total area of the spherical cross section, which is the porosity of the shell layer;
[0050] In a specific embodiment, the thickness of the shell layer is m, the average particle size of the core is n, and n and m satisfy: 1≤n / m≤50;
[0051] and / or, m is 1 μm-5 μm; preferably 1 μm-3 μm;
[0052] And / or, n is 3 μm-15 μm; preferably 4 μm-10 μm.
[0053] Among them, regulating the thickness of the shell layer and the average particle size of the core within the above range can further ensure the compactness of the shell layer structure and prevent the occurrence of side reactions. The thickness of the shell layer and the average particle size of the core can be obtained by scanning electron microscopy (SEM) testing.
[0054] In some embodiments, the secondary particles of the present invention include a dense shell layer and a loose core coated by the dense shell layer, such as Figure 3 As shown, the secondary particle is cut from the middle position, and a cross-sectional backscattering SEM is performed on the cut secondary particle. There is a dividing line between the shell and the inner core. The average particle size of the inner core is the diameter R of the circle formed by the dividing line, which is numerically equal to the straight-line distance from the center of the secondary particle to the dividing line multiplied by 2. The thickness of the shell is the farthest distance r from the dividing line to the outer surface of the secondary particle.
[0055] Exemplarily, m is any value among 1μm, 2μm, 3μm, 4μm, 5μm, etc., or a range consisting of any two of them; n is any value among 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc., or a range consisting of any two of them.
[0056] In order to further ensure that the capacity of the battery is exerted and maintained during charging and discharging at extreme temperatures, in some embodiments, based on the total mass of the positive electrode active material, the percentage content of the conductive carbon material in the shell layer is f, and f satisfies: 2%≤f≤8%;
[0057] And / or, based on the total mass of the positive electrode active material, the percentage content of the conductive carbon material in the inner core is h, and h satisfies: 4%≤h≤10%;
[0058] And / or, the percentage content f of the conductive carbon material in the shell layer is less than the percentage content h of the conductive carbon material in the core layer.
[0059] Among them, when f is less than h, the inner core includes sufficient conductive carbon material, which is beneficial to the construction of the internal electronic network of the secondary particles and can improve the kinetics of the instantaneous reaction of the positive electrode active material. The relatively small amount of conductive carbon material in the shell is beneficial to increase the resistivity of the shell, preventing excessive lithium ions from entering the interior of the secondary particles and destroying the structure of the positive electrode material.
[0060] Exemplarily, f is any value among 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc., or a range consisting of any two of them; h is any value among 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or a range consisting of any two of them.
[0061] In some embodiments, the percentage of the conductive carbon material in the shell is tested by performing EDS on the positive electrode active material and measuring the carbon elements at 3 to 5 different positions on the secondary particle shell profile to obtain the mass percentage of the conductive carbon material in the shell.
[0062] In some embodiments, the percentage of the conductive carbon material in the inner core is tested by performing EDS on the positive electrode active material and measuring the carbon elements at 3 to 5 different positions on the inner core of the secondary particle to obtain the mass percentage of the conductive carbon material in the inner core.
[0063] In a specific embodiment, the D50 of the secondary particles is 3-15 μm, and the average particle size of the primary particles is 200-400 nm. The secondary particles within this particle size range have high density, which helps to further improve the structural stability of the positive electrode active material during long-term charge and discharge.
[0064] The D50 of secondary particles indicates the particle size value corresponding to 50% (by volume) of the cumulative amount in the particle size cumulative distribution curve of secondary particles, which is generally obtained by testing with a laser diffraction particle size distribution instrument. The average particle size of primary particles can be measured by scanning electron microscopy (SEM): use SEM to obtain the surface morphology of primary particles, take multiple test points in the image, measure the size of primary particles in each test point, and calculate the average value.
[0065] The specific surface area of the secondary particles is not particularly limited in the present invention, but in order to ensure the processing characteristics of the positive electrode active material, the specific surface area of the secondary particles is 8 to 15 m 2 / g.
[0066] In a specific embodiment, the average particle size of the conductive carbon material is 10 to 100 nm.
[0067] and / or, the conductive carbon material comprises carbon black,
[0068] And / or, the chemical formula of the positive electrode active material is LiFe xM 1-x PO4; wherein M is at least one of Mn, Co, Ni, and V, and 0≤x≤1.
[0069] On the one hand, since the conductive carbon material has a small average particle size and a large specific surface area, the contact point between the Fe element in the conductive carbon material and the electrolyte can be increased, so that it reacts with the electrolyte before the Fe element in the positive electrode active material, which can further reduce the metal dissolution of the positive electrode active material and improve the high temperature characteristics of the lithium battery; on the other hand, the conductive carbon material as described above can further improve the conductivity of the positive electrode active material while taking into account the cost.
[0070] Exemplarily, the average particle size of the conductive carbon material is any value among 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, etc., or a range consisting of any two of the values.
[0071] Furthermore, the specific surface area of the conductive carbon material is 50 to 2000 m 2 / g range, the moisture content is less than 1000ppm, and the pH value ranges from 7 to 11.
[0072] In a second aspect, the present invention provides a method for preparing the positive electrode active material as described in the first aspect, comprising the following steps:
[0073] A mixture of conductive carbon material, organic carbon source, iron source, M source, lithium source, phosphorus source and solvent is stirred and ball-milled, and then spray-dried at 0.3-0.8 MPa to obtain a precursor of a positive electrode active material, and then sintered at 700-900° C. for 15-30 hours to obtain a positive electrode active material; wherein the solid content of the mixture is not higher than 40wt%.
[0074] In the above preparation method, the mixed material with a solid content not higher than 40wt% is sprayed out in the form of extremely fine water particles through the high pressure of spray drying, and the solvent evaporates rapidly to form a secondary particle precursor with a higher density. After sintering, the positive electrode active material with a specific core-shell structure can be obtained.
[0075] In some embodiments, the spray granulation uses a pressure spray device.
[0076] The specific selection of the above-mentioned organic carbon source, iron source, M source, lithium source, phosphorus source, and solvent is not particularly limited in the present invention, and technicians can select conventional raw materials in the field. In some embodiments, the above-mentioned solvent is deionized water, and the above-mentioned organic carbon source is at least one of glucose, sucrose, asphalt, phenolic resin, starch, cellulose, etc.; the above-mentioned iron source is an iron-containing salt, such as iron sulfate, iron oxide, iron nitrate, etc.; the above-mentioned M source is a salt containing M, for example, nitrate M, phosphate M, sulfuric acid M, chloride M, etc.; the above-mentioned lithium source can be lithium nitrate, lithium chloride, lithium acetate, lithium carbonate, etc.; the above-mentioned phosphorus source can be the same substance as the M source, such as phosphate M.
[0077] In a third aspect, the present invention provides a battery comprising a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises a current collector and a positive electrode active material layer coated on at least one surface of the current collector, wherein the positive electrode active material layer comprises the positive electrode active material described in the first aspect.
[0078] In some embodiments, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material, the negative electrode active material includes graphite, at least a portion of the surface of the graphite is coated with a soft carbon layer, and the thickness of the soft carbon layer is <30 nm.
[0079] Among them, soft carbon has a higher degree of graphitization. The soft carbon layer coated on the graphite surface can improve the kinetic properties of the graphite material, and is conducive to the formation of a dense SEI film, reducing the repeated formation of the SEI film during the charge and discharge process, which affects the performance and structural stability of the negative electrode sheet.
[0080] In some embodiments, the mass content of iron in the soft carbon layer is a, the mass content of iron in the conductive carbon material in the positive electrode active material is b, and a and b satisfy: 2≤b / a≤10;
[0081] a is 0.1ppm-30ppm, preferably 2ppm-15ppm;
[0082] b is 0.5ppm-45ppm, preferably 5ppm-20ppm.
[0083] The iron element of the soft carbon layer in the above embodiment can slow down the deposition of metal elements dissolved in the positive electrode sheet on the surface of the negative electrode sheet, thereby greatly reducing the deposition of metal elements on the surface of the negative electrode sheet, causing the risk of short circuit.
[0084] The source of the iron element in the soft carbon layer is not particularly limited in the present invention. In some embodiments, the doped iron element is derived from an iron-based catalyst introduced during the synthesis of the soft carbon material.
[0085] Although the iron element contained in the negative electrode active material can inhibit the metal elements dissolved in the positive electrode from depositing on the surface of the negative electrode, the iron element in the negative electrode active material should not be too high. If it is higher than or equal to the iron element content in the positive electrode active material, it may cause the iron element in the negative electrode active material to dissolve directly and deposit on the surface of the negative electrode, causing a short circuit in the battery. Therefore, in order to slow down the deposition of the metal elements dissolved in the positive electrode on the surface of the negative electrode without affecting the normal operation of the battery, a and b satisfy: 2≤b / a≤10.
[0086] In some embodiments, the mass content of iron in the soft carbon layer and the mass content of iron in the conductive carbon material can be measured by conventional methods in the art, such as inductively coupled plasma spectrometer (ICP) or energy dispersive spectrometer (EDS).
[0087] In a specific embodiment, in the negative electrode active material, the thickness of the soft carbon layer is less than 30 nm.
[0088] For example, the thickness of the soft carbon layer may be 10 nm, 15 nm, 20 nm, 25 nm, etc. In some embodiments, the D50 of the graphite is 3 to 6 μm, and the specific surface area is 1 to 5 m 2 / g.
[0089] Among them, the use of graphite with smaller particle size in the negative electrode active material helps to shorten the migration path of lithium ions and further improve the kinetic properties of the graphite material.
[0090] For example, the D50 of the graphite can be 3 μm, 4 μm, 5 μm, 6 μm, etc.; the specific surface area of the graphite is 1 m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, etc.
[0091] In some embodiments, the negative electrode active material further comprises hard carbon; the hard carbon has a D50 of 3 to 10 μm and a specific surface area of 5 to 10 m 2 / g.
[0092] In some embodiments, the D50 of the secondary particles of the positive electrode active material is 1 to 3 times the D50 of hard carbon, wherein the particle size matching of the positive and negative electrode particles is beneficial to further improve the transmission rate of lithium ions, thereby improving the kinetic characteristics of the battery.
[0093] For example, the D50 of the hard carbon is 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.; the specific surface area of the hard carbon is 5 m 2 / g, 6m 2 / g, 7m2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, etc.
[0094] In order to further improve the lithium ion diffusion rate of the negative electrode side at low temperature, make the overall polarization of the battery smaller, ensure its rate discharge and capacity at low temperature are better, the capacity retention rate at high temperature is high, and the overall performance is better; in some embodiments, the paste of the negative electrode sheet includes, by mass: 50 to 95 parts of the graphite, 5 to 50 parts of the hard carbon, 1 to 3 parts of the binder, 1 to 3 parts of the conductive agent, and 1 to 3 parts of the dispersant.
[0095] Exemplarily, the conductive agent can be selected from at least one of carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant can be selected from at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium dodecyl sulfate. As for the material of the current collector, the present invention does not make specific restrictions. For example, it can be any one or more of nickel foil, aluminum foil, carbon-coated aluminum foil, chromium foil, and composite foils of the above metals. In some embodiments, the current collector is an aluminum foil or a carbon-coated aluminum foil with a thickness of 8 to 16 μm, and the moisture content of the pole piece is less than 600 ppm.
[0096] In some embodiments, the positive electrode active material layer includes, by mass percentage: 93-98 wt% of the positive electrode active material, 2-5 wt% of the conductive agent, 2-5 wt% of the binder, and 0-1 wt% of the dispersant. The above system has a more complete electronic conductive network, strong adhesion between particles and between particles and current collectors, which is conducive to the performance at low temperatures and the stability of the system during long-term cycles;
[0097] Exemplarily, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant can be selected from at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium dodecyl sulfate.
[0098] In some embodiments, the surface density of the ointment is 6 to 15 mg / cm 2 The compaction density of the positive electrode sheet is 1.6 to 2.3 g / cm 3 Among them, the above-mentioned surface density paste can reduce the diffusion distance of lithium ions, which is helpful for improving the kinetics, and the above-mentioned compacted positive electrode sheet has good contact between particles, which helps to reduce the internal resistance of the system and further improve the rate of lithium ion diffusion.
[0099] As for the thickness, surface density and thickness of the negative electrode active material layer of the above-mentioned negative electrode sheet, the present invention does not make any specific restrictions. However, in order to balance the battery capacity, cycle life and energy density, in a specific embodiment, the thickness of the negative electrode sheet is 40-120 μm, including but not limited to: 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, etc.; the surface density of the negative electrode sheet is 3-10 mg / cm 2 , including but not limited to: 3mg / cm 2 、3.5mg / cm 2 , 4mg / cm 2 , 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 , 6mg / cm 2 、6.5mg / cm 2 , 7mg / cm 2 、7.5mg / cm 2 , 8mg / cm 2 、8.5mg / cm 2 , 9mg / cm 2 、9.5mg / cm 2 、10mg / cm 2 etc.; the thickness of the negative electrode active material layer is 20-60 μm, specifically including but not limited to: 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, etc.
[0100] The battery also includes a diaphragm; the present invention has no particular limitation on the diaphragm, and any known porous diaphragm with electrochemical stability and chemical stability can be selected, for example, it can be at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The diaphragm can be a single layer or multiple layers.
[0101] The battery also includes an electrolyte, which includes an organic solvent and an electrolyte salt. The organic solvent is used as a medium for transmitting ions in the electrochemical reaction, and any organic solvent known in the art for battery electrolyte can be used.
[0102] Exemplarily, the organic solvent may be at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE). In a specific embodiment, two or more of the above organic solvents may be selected.
[0103] As a source of ions, the electrolyte salt can be an electrolyte salt for battery electrolyte known in the art. Exemplarily, the electrolyte salt can be lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluoroantimonate (LiSbF6), lithium difluorophosphate (LiPF2O2), 4,5-dicyano-2-trifluoromethylimidazolium lithium (LiDTI), lithium bis(oxalate)borate (LiBOB), lithium (malonate oxalate)borate (LiMOB), lithium (difluoromalonate oxalate)borate (LiDFMOB), lithium tris(oxalate)phosphate (LiTOP), lithium tris(difluoromalonate)phosphate (LiTDFMP), lithium tetrafluorooxalatephosphate (LiTFOP), lithium nitrate (LiNO3), lithium fluoride (LiF), LiN (SO2R F )2 or LiN(SO2F)(SO2R F ), wherein R F =C n F 2n+1 , n is 2 to 10 and is an integer.
[0104] Exemplarily, the electrolyte may further include an additive, which may be vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone, fluoroethylene carbonate (FEC), trifluoromethyl vinyl carbonate, dimethyl sulfate, vinyl sulfate, vinyl methyl sulfate, propylene sulfate, vinyl sulfite, succinic anhydride, biphenyl, biphenyl ether, toluene, xylene, cyclohexylbenzene, fluorobenzene, p-fluorotoluene, p-fluoroanisole, tert-butylbenzene, tert-amylbenzene, propylene sultone, butane sultone, methylene disulfonate, ethylene glycol bis(propionitrile) ether, hexamethyldisilazane, heptane At least one of methyldisilazane, dimethyl methylphosphonate, diethyl ethylphosphonate, trimethyl phosphate, triethyl phosphate, triphenyl phosphate, triphenyl phosphite, acetonitrile (AN), malononitrile, succinonitrile (SN), glutaronitrile (GN), adiponitrile (ADN), 1,3,6-hexanetricarboxylic acid nitrile, 1,3,5-pentanetricarboxylic acid nitrile, ethylene glycol bispropionitrile ether, 1,4-dicyano-2-butene, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, tricyanobenzene, acrylonitrile, crotononitrile, trans-butenedinitrile, trans-hexenedinitrile, and 1,2-bis(cyanoethoxy)ethane.
[0105] In some embodiments, the electrolyte includes 0.9 mol / L to 1.5 mol / L of lithium salt, 0.5 to 5% of vinylene carbonate, and the balance of an organic solvent, the organic solvent including vinyl carbonate and ethyl methyl carbonate, by total mass percentage of the electrolyte. Exemplarily, the mass ratio of vinyl carbonate to ethyl methyl carbonate is 1 to 6:4 to 7, for example, 3:7, 1:9, 2:8, 4:6, 5:5, 6:4, etc.
[0106] The battery of the present invention can be manufactured according to conventional methods in the art, such as stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, assembling the battery cell through a winding process or a stacking process, and then packaging and baking, injecting the electrolyte, and then hot pressing and other processes to obtain the battery.
[0107] The technical scheme of the present invention is further illustrated below in conjunction with specific examples. All parts, percentages and ratios described in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0108] Example 1
[0109] This example provides a positive electrode active material, including secondary particles formed by stacking primary particles, wherein the chemical composition of the positive electrode active material includes LiFePO4; the secondary particles include a core and a shell formed on the surface of the core, the porosity of the core is greater than the porosity of the shell, and the core and the shell contain carbon black;
[0110] The porosity of the inner core is 15%; the porosity of the shell is 10%; the thickness of the shell is 2 μm, and the average particle size of the inner core is 5 μm; the percentage of carbon black in the shell is 3%, and the percentage of carbon black in the inner core is 4wt%; the carbon black is doped with 5 ppm of iron.
[0111] The D50 of the secondary particles is 10 μm, the D90 is 20 μm, and the D10 is 3 μm; the average particle size of the primary particles is 300 nm; the specific surface area of the secondary particles is 10 m 2 / g; the average particle size of carbon black is 70nm.
[0112] in, Figure 1 The microscopic morphology of the positive electrode active material of this example is shown in FIG. Figure 2 is a cross-sectional microscopic morphology of the positive electrode active material of this example; Figure 3 A schematic diagram showing the identification of the core and shell of the positive electrode active material of this example; Figure 4-7 This is the EDS spectrum of the positive electrode active material in this example.
[0113] The preparation method thereof comprises the following steps:
[0114] 1) Add 1 kg of iron phosphate, 250 g of lithium carbonate, 100 g of glucose, and 15 g of carbon black into a sand mill containing deionized water and stir evenly;
[0115] 2) transferring the slurry obtained in 1) to a nano mill for more thorough grinding, and controlling the fine grinding particle size D50 to be within the range of 250 to 300 nm;
[0116] 3) spray drying the slurry obtained in 2) in a pressure spray device, wherein the solid content of the feed slurry is controlled at 35 wt %, the inlet air temperature is 280° C., and the compressed air pressure is 0.5 MPa, and a spherical particle precursor is obtained after spray drying;
[0117] 4) The above precursors are sintered in a nitrogen atmosphere with a nitrogen purity of more than 99.99%, with a heating rate of 3°C / min, and the temperature is raised to 720°C and kept for 10 hours, and then cooled to 25°C at a cooling rate of 3°C / min to obtain a spherical positive electrode active material.
[0118] Embodiment 2-5
[0119] A positive electrode active material is provided respectively, which is different from Example 1 in that the chemical composition of the positive electrode active material includes LiMn 0.6 Fe 0.4 PO4、LiMn 0.4 Fe 0.6 PO4、LiV 0.1 Fe 0.9 PO4、LiCo 0.5 Fe 0.5 PO4.
[0120] Example 6-26
[0121] A positive electrode active material is provided respectively, which differs from Example 1 in that the parameters in Table 1 are adjusted.
[0122] Comparative Example 1
[0123] This example provides a positive electrode active material, which is different from Example 1 in that the secondary spherical particles have no core-shell structure and the overall porosity is 30%. The preparation method thereof includes:
[0124] 1) Add 1 kg of iron phosphate, 250 g of lithium carbonate, 100 g of glucose, and 15 g of carbon black into a sand mill containing deionized water and stir evenly;
[0125] 2) transferring the slurry obtained in 1) to a nano mill for more thorough grinding, and controlling the fine grinding particle size D50 to be within the range of 250 to 300 nm;
[0126] 3) spray drying the slurry obtained in 2) in a centrifugal spray device, wherein the solid content of the feed slurry is controlled at 35 wt % and the inlet air temperature is 280° C., and a spherical particle precursor is obtained after spray drying;
[0127] 4) The above precursors are sintered in a nitrogen atmosphere with a nitrogen purity of more than 99.99%, with a heating rate of 3°C / min, and the temperature is raised to 720°C and kept for 10 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain a spherical positive electrode active material.
[0128] Comparative Example 2
[0129] This example provides a positive electrode active material, which differs from Example 1 in that the core and the shell do not contain conductive carbon material, and the preparation method thereof comprises the following steps:
[0130] 1) Add 1 kg of iron phosphate, 250 g of lithium carbonate, and 100 g of glucose into a sand mill containing deionized water and stir evenly;
[0131] 2) transferring the slurry obtained in 1) to a nano mill for more thorough grinding, and controlling the fine grinding particle size D50 to be within the range of 250 to 300 nm;
[0132] 3) spray drying the slurry obtained in 2) in a pressure spray device, wherein the solid content of the feed slurry is controlled at 30-40%, the inlet air temperature is 200-300° C., and the compressed air pressure is 0.3-0.8 MPa, and a spherical particle precursor is obtained after spray drying;
[0133] 4) The above precursors are sintered in a nitrogen atmosphere with a nitrogen purity of more than 99.99%, with a heating rate of 3°C / min, and the temperature is raised to 720°C and kept for 10 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain a spherical positive electrode active material.
[0134] Table 1:
[0135]
[0136] Test Example 1
[0137] A series of positive electrode sheets are prepared by using the positive electrode active materials of the above-mentioned embodiments and comparative examples respectively, comprising the following steps:
[0138] (1) By mass, 93.5 wt% of positive electrode active material, 3 wt% of carbon black, 3 wt% of binder polyvinylidene fluoride, and 0.5 wt% of sodium carboxymethyl cellulose were added into a mixing tank and uniformly dispersed in NMP to prepare a positive electrode slurry;
[0139] (2) The positive electrode slurry is evenly coated on the aluminum foil with a carbon coating layer on the surface. The surface density of the coating layer is 6-15 mg / cm 2 ,
[0140] (3) The electrode is baked and then rolled, with a compaction density ranging from 1.6 to 2.3 g / cm 3 ; The positive electrode can be obtained.
[0141] in, Figure 8 4 is a cross-sectional morphology diagram of a positive electrode sheet including the positive electrode active material of Example 1.
[0142] Application Example 1
[0143] The positive electrode sheets of Experimental Example 1 are used to prepare a battery, comprising the following steps:
[0144] Prepare a negative electrode sheet: the negative electrode sheet comprises a copper foil coated with a carbon layer and a paste coated on both surfaces of the copper foil coated with the carbon layer, the paste comprises a negative electrode active material, the negative electrode active material comprises artificial graphite and hard carbon, at least part of the surface of the graphite is coated with a soft carbon layer, and the soft carbon layer is doped with iron element;
[0145] The thickness of the soft carbon layer is 20 nm, and the concentration of iron in the soft carbon layer is 2 ppm; the D50 of the graphite is 5 μm, and the specific surface area is 3.5 m 2 / g; the D50 of the hard carbon is 5μm, and the specific surface area is 5m 2 / g;
[0146] The preparation of the negative electrode sheet includes:
[0147] (1) By mass, 80 wt% of artificial graphite, 15 wt% of hard carbon, 2 wt% of carbon black, 2 wt% of polyacrylic acid, and 1 wt% of sodium carboxymethyl cellulose were added into a mixing tank and uniformly dispersed in deionized water to prepare a negative electrode slurry;
[0148] (2) Evenly apply the negative electrode slurry onto the copper foil. The surface density of the paste layer is 2-8 mg / cm 2 ,
[0149] (3) The electrode is baked and rolled, with a compaction density ranging from 1.2 to 1.6 g / cm 3 ; The negative electrode sheet can be obtained.
[0150] The electrolyte comprises, by mass percentage, 10 wt % of lithium hexafluorophosphate, 3 wt % of vinylene carbonate and the remainder of an organic solvent, wherein the organic solvent comprises vinyl carbonate and ethyl methyl carbonate in a volume ratio of 2:8.
[0151] Assemble the battery: Use the above-mentioned positive electrode sheet, negative electrode sheet, electrolyte and separator to assemble a battery cell with a capacity of 2Ah, and use aluminum-plastic film packaging.
[0152] Application Example 2
[0153] The same as Application Example 1, except that: the positive electrode sheet containing the positive electrode active material of Example 1 in Test Example 1 is used, and the negative electrode sheet is basically the same as Application Example 1, except that: the thickness of the soft carbon layer is 40nm.
[0154] Application Example 3
[0155] The same as Application Example 1, except that: the positive electrode sheet containing the positive electrode active material of Example 1 in Test Example 1 is used, and the negative electrode sheet is basically the same as Application Example 1, except that: the graphite does not include a soft carbon layer.
[0156] Performance Testing
[0157] The following performances of the test application example battery are shown in Table 2:
[0158] High temperature performance test method: After fully charging the battery cell, place it in a 60°C constant temperature box for 60 days, and record the battery residual capacity (the remaining capacity of the battery after 60 days of storage) retention rate and recovery capacity (after 60 days of storage, perform 1C charge and discharge at room temperature, the capacity is recovered, and it is recorded as the recovery capacity) retention rate;
[0159] Low temperature performance test method: After fully charging the battery cell at room temperature, place it in a -20℃ constant temperature box for 4 hours, discharge it at a 1C rate, and record the discharge capacity retention rate, that is, the ratio of the -20℃ / 1C discharge capacity to the room temperature discharge capacity.
[0160] Table 2:
[0161]
[0162]
[0163] It can be seen from Table 2 that, compared with the comparative example, the battery made of the positive electrode active material of the embodiment has both high and low temperature characteristics, specifically, the capacity and energy are higher at low temperatures, and the storage and cycle performance are better at high temperatures.
[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode active material, characterized in that: The positive electrode active material includes primary particles and secondary particles formed by stacking the primary particles. The secondary particles include an inner core and a shell located on the surface of the inner core. The inner core and the shell include conductive carbon material. The mass content of iron in the conductive carbon material is 0.5ppm to 45ppm.
2. The positive electrode active material according to claim 1, characterized in that The porosity of the inner core is 5% to 30%, and / or the porosity of the shell layer is 2% to 15%, and / or the porosity of the inner core is greater than the porosity of the shell layer.
3. The positive electrode active material according to claim 1, characterized in that The thickness of the shell layer is m, the average particle size of the core is n, and n and m satisfy: 1≤n / m≤50; and / or, m is 1 μm-5 μm; preferably 1 μm-3 μm; And / or, n is 3 μm-15 μm; preferably 4 μm-10 μm.
4. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the positive electrode active material, the percentage content of the conductive carbon material in the shell layer is f, and f satisfies: 2%≤f≤8%; And / or, based on the total mass of the positive electrode active material, the percentage content of the conductive carbon material in the inner core is h, and h satisfies: 4%≤h≤10%; And / or, based on the total mass of the positive electrode active material, the percentage content f of the conductive carbon material in the shell layer is less than the percentage content h of the conductive carbon material in the core layer.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The D50 of the secondary particles is 3 to 15 μm, and the average particle size of the primary particles is 200 to 400 nm.
6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The average particle size of the conductive carbon material is 10 to 100 nm. and / or, the conductive carbon material comprises carbon black, And / or, the chemical formula of the positive electrode active material is LiFe x M 1-x PO4; wherein M is at least one of Mn, Co, Ni, and V, and 0≤x≤1.
7. A method for preparing a positive electrode active material according to any one of claims 1 to 6, characterized in that: The following steps are involved: A mixture of conductive carbon material, organic carbon source, iron source, M source, lithium source, phosphorus source and solvent is stirred and ball-milled, and then spray-dried at 0.3-0.8 MPa to obtain a precursor of a positive electrode active material, and then sintered at 700-900° C. for 15-30 hours to obtain a positive electrode active material; wherein the solid content of the mixture is not higher than 40wt%.
8. A battery comprising a negative electrode sheet and a positive electrode sheet, wherein the positive electrode sheet comprises a current collector and a positive electrode active material layer coated on at least one surface of the current collector, characterized in that: The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 6.
9. The battery according to claim 8, characterized in that The negative electrode sheet comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises graphite, at least a portion of the surface of the graphite is coated with a soft carbon layer, and the thickness of the soft carbon layer is less than 30 nm.
10. The battery according to claim 9, characterized in that The mass content of iron in the soft carbon layer is a, the mass content of iron in the conductive carbon material in the positive electrode active material is b, and a and b satisfy: 2≤b / a≤10; a is 0.1ppm-30ppm, preferably 2ppm-15ppm; b is 0.5ppm-45ppm, preferably 5ppm-20ppm.